Scleral buckling in retinal detachment due to retinal dialysis – A vitreoretina fellow’s perspective - Akshaya Balaji; Saurabh Verma; Nawazish Shaikh; Shorya V Azad; Parmanand Kumar; Rohan Chawla; Vinod Kumar (Indian Journal of Ophthalmology)
Purpose: To analyze the efficacy of scleral buckling in the hands of vitreo-retina (VR) fellows under training in eyes with retinal detachment associated with retinal dialysis and analyze the patient and retinal characteristics in these eyes. Methods: We carried out a retrospective consecutive case review at a tertiary eye care center in North India. Records of all the patients who had undergone scleral buckling (SB) for retinal dialysis-associated rhegmatogenous retinal detachment by VR fellows (with less than 2 years’ experience) between January 2017 and January 2020 were reviewed. Results: Fifty-three eyes of 53 patients with a mean age of 20.77 years were analyzed. Of the patients, 73.58% were males. History of eye trauma was present in 71.69% patients. A total of 21 residents operated these 53 eyes. SB was able to achieve retinal attachment in a single surgery in 84.9% (45/53) eyes. Mean preoperative best corrected visual acuity was 1.9 ± 1.05 log of minimum angle of resolution (logMAR), which improved postoperatively to 1.07 ± 0.72 logMAR (P < 0.001). Surgical success rate was 85.71% (24/28) in eyes with no proliferative vitreoretinopathy (PVR), 66.66% (2/3) in eyes with PVR-A, 91.66% (11/12) in eyes with PVR-B, and 80% (8/10) in eyes with PVR-C1. Fifty-two eyes had a single dialysis and one eye had two separate dialysis. Six eyes had giant retinal dialysis (dialysis greater than 3 clock hours) and all were due to trauma. Five patients had retinal dialysis in the fellow eye and were diagnosed with bilateral idiopathic retinal dialysis. Conclusion: Scleral buckling is a safe and effective management for retinal dialysis retinal detachment even in the hands of VR fellows under training.